(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the structure, habitat, reproductive characteristics and importance of blue-green algae (Cyanophyta). Their cell structure, pigment system, physiological properties and ecological adaptability are scientifically covered. The biological role of representatives such as Nostochia and Oscillatoria, their nitrogen fixation properties and importance in human activity are also analyzed.